1981
DOI: 10.1017/s000335610003172x
|View full text |Cite
|
Sign up to set email alerts
|

Some behavioural deviations in weaned domestic pigs: persistent inguinal nose thrusting, and tail and ear biting

Abstract: Groups of pigs were observed from weaning to marketing for the incidence of tail and/or ear biting and persistent inguinal nose thrusting. The 16 groups included single and mixed litters, single or mixed-sex ratios, and comprised up to 12 pigs; 14 of the groups showed biting behaviour and 12 groups showed persistent inguinal nose thrusting behaviour. The onset of biting appeared from 0 to 44 days after weaning, and persistent inguinal nose thrusting was first observed 4 to 22 days after weaning.There was a sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
2
2

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 6 publications
1
34
2
2
Order By: Relevance
“…Moreover, it is uncertain if the chosen biters were the actual initiators of the behaviour. Tail biting is known to spread visually (Blackshaw, 1981), and characteristics of followers may differ from those of the instigators. A high infection pressure seemed to be present on the farm, as suggested by both pathological findings and a high prevalence of anaemia characterized by low MCHC, which is an indication of chronic inflammation (Friendship and Henry, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is uncertain if the chosen biters were the actual initiators of the behaviour. Tail biting is known to spread visually (Blackshaw, 1981), and characteristics of followers may differ from those of the instigators. A high infection pressure seemed to be present on the farm, as suggested by both pathological findings and a high prevalence of anaemia characterized by low MCHC, which is an indication of chronic inflammation (Friendship and Henry, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Tail biting occurs in outbreaks Damaging tail biting occurs in a sporadic way, in unpredictable 'outbreaks', rather like an infectious disease (Blackshaw, 1981). For example, in one study using abattoir data, 'high incidence farms' were identified at one point in time, but when a similar 'high incidence' list was made a few months later, most of the farms were different -although there were a few farms with a persistent problem .…”
Section: Tail Biting: Why It Remains An Intractable Problemmentioning
confidence: 99%
“…Over time, biting pigs may continue or escalate their biting of existing victims, but also begin biting other pigs in the group (Niemi et al, 2011). Additionally, other pigs in an affected pen begin tail biting too, perhaps because they copy the behaviour (social facilitation; Blackshaw, 1981) or the D'Eath, Arnott, Turner, Jensen, Lahrmann, Busch, Niemi, Lawrence and Sandøe bitten tails might stimulate investigation and biting (stimulus enhancement; Fraser, 1987a). Although never formally studied, there appears to be considerable variation in the rate at which a pig increases its tail biting behaviour, and in the rate of spread to new biters.…”
Section: Tail Biting: Why It Remains An Intractable Problemmentioning
confidence: 99%
“…These include belly-nosing, tail-and ear-biting (Blackshaw, 1981;Breuer et al, 2005), aggression (Andersen et al, 2000) and mounting behaviour performed by entire males (Boyle and Bjorklund, 2007;Conte et al, 2010). These behaviours can directly result in injury, lameness, infection and abscessation (Wallgren and Lindahl, 1996;Rhydmer et al, 2004;Turner et al, 2006) and are often associated with chronic stress (de Jong et al, 2000) and immunosuppression (de Groot et al, 2001).…”
Section: Introductionmentioning
confidence: 99%